2013
DOI: 10.1038/ncomms3757
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock protein dysregulation is associated with functional and pathological TDP-43 aggregation

Abstract: Conformational disorders are involved in various neurodegenerative diseases. Reactive oxygen species (ROS) are the major contributors to neurodegenerative disease; however, ROS that affect the structural changes in misfolded disease proteins have yet to be well characterized. Here we demonstrate that the intrinsic propensity of TDP-43 to aggregate drives the assembly of TDP-43-positive stress granules and soluble toxic TDP-43 oligomers in response to a ROS insult via a disulfide crosslinking-independent mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…Intriguingly, Chd1 is linked to gene induction following stress [30, 32], and molecular chaperones are crucial in neurodegenerative processes [3335]. TDP-43, like numerous other degenerative disease proteins, is aggregation-prone, and several heat shock proteins protect against its toxicity [3640]. In accordance with these studies, we found that upregulation of Hsc4 and Hsp68 suppressed TDP-43 toxicity (Figure S2A, B).…”
Section: Resultssupporting
confidence: 82%
“…Intriguingly, Chd1 is linked to gene induction following stress [30, 32], and molecular chaperones are crucial in neurodegenerative processes [3335]. TDP-43, like numerous other degenerative disease proteins, is aggregation-prone, and several heat shock proteins protect against its toxicity [3640]. In accordance with these studies, we found that upregulation of Hsc4 and Hsp68 suppressed TDP-43 toxicity (Figure S2A, B).…”
Section: Resultssupporting
confidence: 82%
“…To this end, we treated HeLa cells with various compounds described in the literature that were shown to induce pathological changes in TDP-43, though not necessarily TDP-43 truncation. We tested the proteasome inhibitor MG132 (10 μM, 4 h) [13, 42], the oxidative stressors hydrogen peroxide (1 mM, 60 min) [43] and sodium arsenite (0.5 mM, 30 min) [44], the sarco-endoplasmic reticulum Ca 2+ -ATPase inhibitor thapsigargin (1 μM, 60 min) [15, 29] and the oxidative and osmotic stressor D-sorbitol (0.4 M, 60 min) [14]. However, while MG132 as well as thapsigargin and D-sorbitol have been described to promote cleavage of TDP-43, we observed a reduction of full-length TDP-43 as well as the formation of a 35 kDa fragment (CTF35) with D-sorbitol only (Fig 2) [14, 29, 42].…”
Section: Resultsmentioning
confidence: 99%
“…Heat‐shock protein defects have been implicated in PD (Yang et al ., 2015) and AD (Ou et al ., 2014), and HspB1 mutations are associated with familial motor neuron diseases (Muranova et al ., 2015). Hsp90 and its co‐chaperones regulate tau and Aβ processing (Blair et al ., 2014), and Hsp90 may specifically protect TDP‐43 from ROS‐induced aggregation (Chang et al ., 2013a). The mitochondrial HSP70, also called ‘stress‐70’ or ‘mortalin’, is implicated in PD and in vitro longevity (Wadhwa et al ., 2015).…”
Section: Discussionmentioning
confidence: 99%